“One government, one flag, one destiny:” Union soldiers’ ideological support of Lincoln’s reelection - Bach, Ryan Martin (Kansas State University, 2015)
This thesis examines the reasons Union soldiers voted overwhelmingly for Abraham Lincoln in the presidential election of 1864. This thesis bridges the gap between the emerging disagreements within the historiography of the soldier vote in 1864. The disagreements thus far deal with the role of emancipation in the Union soldier’s decision-making process versus the role of other issues, particularly whether or not the war effort should have been continued on to ultimate victory. By extension, the argument also deals with whether or not Union soldiers adhered to the Republican Party’s ideology in making their decision. Through analysis of primary sources including Union soldiers’ letters and diaries, the answer that emerges is that Union soldiers adhered to Republican ideology as outlined by Republican campaign materials as well as their party platform in making their decision for president. This thesis ultimately concludes that a focus on any one reason or another that soldiers chose Lincoln misses the larger picture.
Keywords: Abraham Lincoln; election of 1864; Union soldiers; soldier voting; American History (0337); History (0578)